2019
DOI: 10.1074/mcp.ra119.001534
|View full text |Cite
|
Sign up to set email alerts
|

Bisecting GlcNAc Is a General Suppressor of Terminal Modification of N-glycan*[S]

Abstract: Glycoproteins are decorated with complex glycans for protein functions. However, regulation mechanisms of complex glycan biosynthesis are largely unclear. Here we found that bisecting GlcNAc, a branching sugar residue in N-glycan, suppresses the biosynthesis of various types of terminal epitopes in N-glycans, including fucose, sialic acid and human natural killer-1. Expression of these epitopes in N-glycan was elevated in mice lacking the biosynthetic enzyme of bisecting GlcNAc, GnT-III, and was conversely sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
77
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 66 publications
15
77
1
1
Order By: Relevance
“…The alterations in gene expression and glycome levels are also consistent with a previous report showing the increased degree of MGAT3 and MGAT5 activities in the tissues of pancreatic carcinoma patients (45). Notably, a more recent study has demonstrated that the introduction of bisecting GlcNAc suppresses terminal modifications of N-glycans such as fucosylation and sialylation in genetically modified mice (46). The present tissue glycomic profiling results are consistent with this previous report in that the increased level of bisecting GlcNAc was accompanied by decreased fucosylation.…”
Section: Discussionsupporting
confidence: 91%
“…The alterations in gene expression and glycome levels are also consistent with a previous report showing the increased degree of MGAT3 and MGAT5 activities in the tissues of pancreatic carcinoma patients (45). Notably, a more recent study has demonstrated that the introduction of bisecting GlcNAc suppresses terminal modifications of N-glycans such as fucosylation and sialylation in genetically modified mice (46). The present tissue glycomic profiling results are consistent with this previous report in that the increased level of bisecting GlcNAc was accompanied by decreased fucosylation.…”
Section: Discussionsupporting
confidence: 91%
“…The second feature of bisecting GlcNAc is its inhibitory effects on other glycosyltransferases. The enzymes responsible for producing other N-glycan branches (e.g., GnT-IV, GnT-V, and FUT8) as well as the enzymes acting on N-glycan terminals (fucosyltransferases, sialyltransferases and biosynthetic enzymes for human natural killer-1 epitope) are inhibited partially or completely by the presence of a bisecting GlcNAc in N-glycan [54][55][56]. This is probably because the presence of bisecting GlcNAc alters glycan conformation and restricts preferable conformers of N-glycan.…”
Section: Functional Overview Of Gnt-iiimentioning
confidence: 99%
“…Molecular dynamic simulation, NMR analysis, and X-ray crystallography suggest that bisected N-glycans tend to prefer back-fold conformations in which the α1-6 branch flips back to the reducing end [56][57][58][59][60]. Our MS glycan analysis revealed increases in various terminal epitopes of N-glycans in Mgat3-knockout brain, which is concomitant with complete loss of bisecting GlcNAc, suggesting that one of the physiological functions of bisecting GlcNAc is to suppress formation of mature and complex N-glycans [56]. Similarly, Dr. Gu's group reported that the level of bisecting GlcNAc is negatively correlated with the level of sialylation in various cell lines [61].…”
Section: Functional Overview Of Gnt-iiimentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, bisecting GlcNAc has been recognized as a suppressor of terminal modifications of N-glycan, which may further influence biological functions of glycans on glycoproteins [31]. However, the effects of bisecting GlcNAc on functional properties of IgG are not well understood.…”
Section: Of 15mentioning
confidence: 99%